High success rate in salvage of catheter-related bloodstream infections due to Staphylococcus aureus, on behalf of project group of Italian society of nephrology. Issue 3 (May 2020) - Mandolfo, Salvatore; Anesi, Adriano; Maggio, Milena; Rognoni, Vanina; Galli, Franco; Forneris, Giacomo
Background: Catheter-related bloodstream infections caused by Staphylococcus aureus represent one of the most fearful infections in chronic haemodialysis patients with tunnelled central venous catheters. Current guidelines suggest prompt catheter removal in patients with positive blood cultures for S. aureus . This manoeuvre requires inserting a new catheter into the same vein or another one and is not without its risks. Methods: A protocol based on early, prompt diagnosis and treatment has been utilized in our renal unit since 2012 in an attempt to salvage infected tunnelled central venous catheters. We prospectively observed 247 tunnelled central venous catheters in 173 haemodialysis patients involving 167, 511 catheter days. Results: We identified 113 catheter-related bloodstream infections (0.67 episodes per 1000 days/tunnelled central venous catheter). Forty were caused by S. aureus, including 19 by methicillin-resistant S. aureus (79% saved) and 21 by methicillin-sensitive S. aureus (90% saved), of which 34 (85%) were treated successfully. Eight recurrences occurred and six (75%) were successfully treated. A greater than 12 h time to blood culture positivity for S. aureus was a good prognostic index for successful therapy and tunnelled central venous catheter rescue. Conclusion: Our data lead us to believe that it is possible to successfully treat catheter-related bloodstream infection caused by S. aureus and to avoid removing the tunnelled central venous catheter in many more cases than what has been reported in the literature. On the third day, it is mandatory to decide whether to replace the tunnelled central venous catheter or to carry on with antibiotic therapy. Apyrexia and amelioration of laboratory parameters suggest continuing systemic and antibiotic lock therapy for no less than 4 weeks, otherwise, tunnelled central venous catheter removal is recommended.